Determining the Air Gap Length of an Axial Flux Wound Rotor Synchronous Generator - Multi, Abdul; Garniwa, Iwa; Sudibyo, Uno Bintang (UI Scholars Hub, 2013)
The air gap length of the designed axial flux wound rotor (AFWR) synchronous generator is determined properly according to the design parameters. One of the distinct advantages of an axial flux (AF) machine is its adjustable air gap. An AF generator’s performance might be controlled by adjusting its air gap. The designed generator has a smallscale capacity that has 1 kW, 380 V, and 50 Hz. The windings are laid into slots made from laminated core. The slots are carved in the face of the stator and rotors. The generator has a single-double-sided slotted wound stator sandwiched between twin rotors. The effect of air gap changes on its performance can be seen from the calculation results using the given equations. The results reveal electric quantities suited to the machine’s effective performance. The smaller the air gap, the greater the efficiency and power factor and the smaller the armature current and voltage. The efficiency and armature current for 0.1 cm air gap are 85.30 % and 1.815 A, respectively.